The Investigation of the Effect of Hyperglycemic Changes on Psychophysical Measurements of Visual Function in Pseudophakic People Living with Diabetes Mellitus - Majola L; Munsamy AJ (Clinical Optometry, 2021)
Lindokuhle Majola,1 Alvin J Munsamy2 1Department of Health, Port Shepstone, South Africa; 2Discipline of Optometry, School of Health Science, University of KwaZulu-Natal, Durban, South AfricaCorrespondence: Lindokuhle MajolaDepartment of Health, Ugu District, PO Box 951, Hibberdene, Port Shepstone, 4220, South AfricaTel +27 79 347 8540Email lindokuhle.majola2@gmail.comAlvin J MunsamyDiscipline of Optometry, School of Health Science, University of KwaZulu-Natal, Private Bag X54001, Durban, 4000, South AfricaTel +27 31 260 7352Fax +27 31 260 7666Email Munsamya1@ukzn.ac.zaPurpose: The purpose of this study was to show the effect of increasing blood glucose level (BGL) on psychophysical visual function represents by visual acuity and contrast sensitivity in pseudophakic people living with diabetes (PDM).Study Design: This was quasi-experimental, quantitative study using a pretest–posttest approach.Methods: The study was conducted at Gamalakhe community health centre located in Gamalakhe township and included a sample of 50 pseudophakic people living without diabetes mellitus (PWDM) and 50 pseudophakic PDM. BGL as well as psychophysical measurements of visual function were measured preprandial and postprandial. Visual acuity (VA) was measured at distance (4 m) and near (40 cm) using logMAR VA charts, and contrast sensitivity (CS) was measured at 50 cm using a Mars chart. The data collected were captured and subsequently analyzed using SPSS version 25.Results: Glycemic changes measured preprandial and postprandial observed a mean increase of 2.06± 1.35 mmol/L (p=0.350) and 1.08± 0.47 mmol/L (p=0.291) in pseudophakia PDM and pseudophakic PWDM, respectively. CS showed a mean increase of 0.01± 0.10 (p=0.23) and 0.002± 0.02 (p=0.19) log units in PDM and PWDM, respectively; however, the independent t-test showed this was insignificant between PDM and PWDM (p=0.27). A insignificant mean increase of 0.01± 0.04 log units (p=0.25) and 0.001± 0.01 (p=0.32) in distance VA of pseudophakic PDM and PWDM was found, respectively. A mean increase of 0.001± 0.01 log units (p=0.32) and 0.01± 0.03 (p=0.06) near logMAR VA of pseudophakic PDM and PWDM was found, respectively.Conclusion: Acute hyperglycemic changes do not result in overall significant changes in visual acuity and contrast sensitivity in pseudophakic PDM and PWDM for an increase in glycemia of 2 mmol/L. We recommend studies investigate if changes occur for glycemic increases exceeding 2 mmol/L.Keywords: diabetes mellitus, contrast sensitivity, visual acuity, pseudophakia